Research Project as a Means of Preparation of the Future Primary School Teachers to Conducting Pedagogical Research - Oksana Shkvyr (Pedagogical Discourse, 2013)
The problem of preparation of the future primary school teachers to conducting pedagogical researches has been actualized in the article. Development by the students research projects has been determined as an important means of the mentioned preparation. The content of the notion «Research Project» and peculiarities of the project research activity have been revealed in the article. The author’s structure of development of research projects in the process of study of educational disciplines has been offered. By the example of study of the course «Topical Problems of Primary Education» technology of performing of research projects has been studied.